Impact of Gamma, Neutron, Ion, and Electron Irradiation on Structure and Properties of Graphene - R. V. Biliak (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ)
This article discusses studies of the effects of various types of radiation, including γ-radiation, neutron, ion, and electron irradiation, on graphene and graphene-based devices. The study of graphene's response to radiation is crucial because of its potential applications in fields such as nuclear power and space exploration, where the impact of radiation is significant.